Effect of Nickel Oxide on the Conductivity of Polymer Blend Electrolyte Doped with Sodium Iodide and Its Application in Dye-Sensitized Solar Cell - Subramaniam, Ramesh T; M. Saidi, Norshahirah; Omar, Fatin Saiha; Kasi, Ramesh (Malaysian Journal of Science, 2019)
Ionic conductivity of electrolyte is one of the factor that influences the efficiency of dye-sensitized solar cell (DSSC). Herein, gel polymer electrolyte (GPE) consist of polyacrylonitrile (PAN), poly(1-vinylpyrrolidone-co-vinyl acetate) (P(VP-co-VAc)), sodium iodide (NaI) dopant and nickel oxide (NiO) additive was prepared using solution casting method. The ionic conductivity study revealed that after the inclusion of NiO, the conductivity was increased from 2.33 mS cm-1 (for polymer blend) to 4.84 mS cm-1. Besides the dielectric properties, the electrical modulus study was conducted to analyse the effect of electrode polarization and ionic conductivity of the GPE. Under the exposure of AM 1.5, the fabricated DSSC utilizing the prepared GPE exhibited photoenergy conversion efficiency of 3.98% with a short circuit current density (JSC) of 15.03mA cm-2, open circuit voltage (VOC) of 0.57 mV and fill factor (FF) of 44.0 %.